Targeted Prostate Biopsies Overestimate International Society of Urological Pathology Grade Group, Particularly in Smaller Tumors - Lisa J. Kroon; Ivo I. de Vos; Charlotte F. Kweldam; Monique J. Roobol; Geert J.L.H. van Leenders; Roderick C.N. van den Bergh (European Urology Open Science)
Compared with systematic biopsy of the prostate, magnetic resonance imaging (MRI)-targeted biopsies are associated with lower rates of upgrading and higher rates of downgrading between biopsy tissue and radical prostatectomy (RP) specimen International Society of Urological Pathology (ISUP) grade group (GG). Higher rates of downgrading could indicate overtreatment for some patients. We hypothesized that concordance rates between biopsy and RP are different per MRI tumor volume. We conducted an explorative retrospective study to identify the risk factors for downgrading, using RP specimens as the reference standard, in a large regional prostate collaboration. Among 616 patients, pathological concordance was seen in 58% and downgrading in 15%. The risk of downgrading was 18% for tumors of 0–10 mm, 14% for 10–20 mm, and 14% for >20 mm. In a multivariable analysis among patients with targeted biopsy GG ≥2, with covariates including clinical tumor stage, prostate-specific antigen (PSA), maximal MRI index lesion diameter, number of positive target biopsies, and GG at targeted biopsy, the statistically significant predictors for downgrading were PSA, maximum MRI index lesion diameter, and target biopsy GG. A lower risk of downgrading was seen in larger tumors (odds ratio per millimeter 0.95, 95% confidence interval 0.91–1.00, p = 0.033). This study suggests that an overestimation of GG on biopsy is most common in smaller MRI lesions. This information is important in clinical decision-making, mainly in deciding on active surveillance versus active therapy or the indication for additional imaging for cancer staging. Patient summary: In this report, we examined risk factors that could explain why some patients have higher pathological grading at prostate biopsy than on the whole prostate specimen after surgical removal. We found that patients with prostate biopsies that are targeted at small lesions on magnetic resonance imaging and patients who had high biopsy grading had a higher risk of having lower grading of their surgical specimens.